Aceh Under Syari’ah: Faith, Law, and Society - Arifin, Ridwan; Idris, Siti Hafsyah; Sani, Tajudeen; Nte, Ngaboawaji Daniel (Indonesia Discourse, 2024)
The implementation of Syari'ah law in Aceh has been a significant and often contentious aspect of the region’s post-conflict reconstruction process. Following the 2005 peace agreement between the Indonesian government and the Free Aceh Movement (Gerakan Aceh Merdeka, GAM), Aceh became the only province in Indonesia with the legal mandate to enforce Syari'ah law. This research explores the intersection of faith, law, and society in Aceh, examining how Syari'ah has reshaped not only legal frameworks but also the daily lives of its people. Despite its importance, there exists a gap in understanding the broader social implications of Syari'ah’s implementation, particularly its effects on gender, civil rights, and the overall social fabric. Previous studies have focused on the legal and political aspects, yet little attention has been given to the lived experiences of Acehnese citizens under this system. This study aims to address this gap by analyzing the societal transformations resulting from Syari'ah law, specifically focusing on how religious practices and legal structures interact within the Acehnese context. The urgency of this research lies in the increasing global attention to Islamic legal systems and their integration into state governance, offering a comparative lens for other regions pursuing similar models. Novel in its approach, the research contributes to a deeper understanding of the real-world implications of Syari'ah law on faith, law, and society, with particular attention to its effects on minority groups and social cohesion. Ultimately, it highlights the broader implications for peace-building in post-conflict societies, offering valuable insights for scholars and policymakers alike.